(untitled) (Clinics, 2016)
Obstructive sleep apnoea syndrome is a type of sleep-disordered breathing that affects 1 to 5% of all children. Pharyngeal and palatine tonsil hypertrophy is the main predisposing factor. Various abnormalities are predisposing factors for obstructive sleep apnoea, such as decreased mandibular and maxillary lengths, skeletal retrusion, increased lower facial height and, consequently, increased total anterior facial height, a larger cranio-cervical angle, small posterior airway space and an inferiorly positioned hyoid bone. The diagnosis is based on the clinical history, a physical examination and tests confirming the presence and severity of upper airway obstruction. The gold standard test for diagnosis is overnight polysomnography. Attention must be paid to identify the craniofacial characteristics. When necessary, children should be referred to orthodontists and/or sleep medicine specialists for adequate treatment in addition to undergoing an adenotonsillectomy.